2010
DOI: 10.1002/hep.24029
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic cells attenuate fulminant hepatitis by priming Kupffer cells to produce interleukin-10 through membrane-bound TGF-β

Abstract: The liver, a unique tolerogenic organ, is regarded as the site to trap and destroy aging erythrocytes and activated T cells. However, to date, the mechanisms for why the liver is tolerogenic and whether liver Kupffer cells (KC) are critical phagocytes for apoptotic cells (AC) contributing to the liver immunosuppression remain unclear. Here we report that KC is the main phagocyte for AC in the liver. Contact of AC inhibits proinflammatory cytokine but enhances anti-inflammatory cytokine production of KC in resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 45 publications
1
83
1
3
Order By: Relevance
“…First, we found that apoptosis barely occurred in macrophages with ectopic miR-145, and there was no significant difference in comparison with the control group or miR-143 overexpression group (data not shown). Second, the data from previous studies (39,40) indicate that the activities of p38 and ERK MAPK are crucial for apoptotic cell-induced IL-10 transcription and protein production; and as shown in Fig. 4A, we did not detect significant activation of p38 or ERK in macrophages with ectopic miR-145 (at 0 time point).…”
Section: Discussionsupporting
confidence: 51%
“…First, we found that apoptosis barely occurred in macrophages with ectopic miR-145, and there was no significant difference in comparison with the control group or miR-143 overexpression group (data not shown). Second, the data from previous studies (39,40) indicate that the activities of p38 and ERK MAPK are crucial for apoptotic cell-induced IL-10 transcription and protein production; and as shown in Fig. 4A, we did not detect significant activation of p38 or ERK in macrophages with ectopic miR-145 (at 0 time point).…”
Section: Discussionsupporting
confidence: 51%
“…KC production of IL‐10 may be up‐regulated by encapsulated platelets; therefore, when KC are first activated by liver injury such administered platelets cause increased secretion of IL‐10 and down‐regulation of ROS 34. Interestingly, increased phagocytosis by KC leads to attenuation of hepatitis through IL‐10‐mediated suppression of ROS and inflammatory cytokines 35. In conclusion, as pointed out by Krenkel and Tacke 26, available data from experiments in animals and early clinical trials suggest strongly that targeting pathogenic Kupffer cells may be a novel promising approach in acute and chronic liver diseases.…”
Section: Phages Kupffer Cells and Immune Homeostasismentioning
confidence: 99%
“…Apoptotic splenocytes were obtained as previously described. 39 Briefly, splenocytes ( 5310 6 ) were suspended in 5 ml PBS in a 10-cm-diameter Petri plate and exposed to a 40 W UV (320 nm) source at a distance of 40 cm for 10 min. After irradiation, splenocytes were resuspended in RPMI-1640 (with 10% fetal bovine serum) and cultured for 4 h before infusion.…”
Section: Cell Preparationmentioning
confidence: 99%